The Effect of Demographic Characteristics and Personality Traits on Financial Risk Tolerance. A Case Study of Lower Dir - Waqar; Shah, Mukamil; Zia, Manzar (iRASD Journal of Economics, 2023)
This research investigates the intricate relationships between financial risk tolerance, personality traits, and demographic characteristics among investors in Lower Dir. By acknowledging the crucial role of these factors in shaping investment decisions, our analysis of 284 participants' data reveals that age, education, conscientiousness, and neuroticism significantly impact financial risk tolerance. On the other hand, gender, monthly income, openness to experience, and agreeableness show weaker or insignificant associations. These findings provide essential insights for devising effective financial planning and investment strategies. To further explore these relationships, future research should consider longitudinal or experimental approaches and larger sample sizes.